2010
DOI: 10.4319/lo.2010.55.4.1697
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing zooplankton size structure at contrasting temperatures in coastal shallow lakes: Implications for effects of climate change

Abstract: We assessed the importance of temperature, salinity, and predation for the size structure of zooplankton and provided insight into the future ecological structure and function of shallow lakes in a warmer climate. Artificial plants were introduced in eight comparable coastal shallow brackish lakes located at two contrasting temperatures: cold-temperate and Mediterranean climate region. Zooplankton, fish, and macroinvertebrates were sampled within the plants and at open-water habitats. The fish communities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 41 publications
(70 reference statements)
6
119
5
Order By: Relevance
“…Accordingly, we found that summer air temperatures, especially in April where fish are spawning, have become warmer in the region during the study period, and the changes were significantly correlated with the abundances of small (positive) and large fish (negative). Concurrently, field research undertaken in numerous European lakes has shown a significant decline in fish body size with decreasing latitude and thus higher temperatures [20,21,25,61]. The change in fish body size might be a result of improved recruitment of fish due to higher temperatures in spring and likely also as a result of increasing survival of young fish during winter due to a shorter ice cover period [29].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we found that summer air temperatures, especially in April where fish are spawning, have become warmer in the region during the study period, and the changes were significantly correlated with the abundances of small (positive) and large fish (negative). Concurrently, field research undertaken in numerous European lakes has shown a significant decline in fish body size with decreasing latitude and thus higher temperatures [20,21,25,61]. The change in fish body size might be a result of improved recruitment of fish due to higher temperatures in spring and likely also as a result of increasing survival of young fish during winter due to a shorter ice cover period [29].…”
Section: Discussionmentioning
confidence: 99%
“…Global warming reinforces the eutrophication of already eutrophic lakes (Moss et al, 2011), with significant changes in lake food web structure and community composition Meerhoff et al, 2007;Brucet et al, 2010;Jeppesen et al, 2010a, b;Brucet et al, 2012;Meerhoff et al, 2012), and causes higher proportions of cyanobacteria in summer (Wagner & Adrian, 2009;Kosten et al, 2012). In the Mediterranean climate zone and other areas with semi-arid desert climates, changes in water level, hydraulic retention time and salinity associated with warming may have considerable further effects on lake ecosystem structure and dynamics (reviews by Wantzen et al, 2008, andBrucet et al, 2010;Zohary & Ostrovsky, 2011;Brucet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean climate zone and other areas with semi-arid desert climates, changes in water level, hydraulic retention time and salinity associated with warming may have considerable further effects on lake ecosystem structure and dynamics (reviews by Wantzen et al, 2008, andBrucet et al, 2010;Zohary & Ostrovsky, 2011;Brucet et al, 2012). Besides nutrient loading, evaporative up-concentration of nutrients in reduced water volumes becomes an additional factor enhancing eutrophication under warmer conditions (Ö zen et al, 2010), and longer water residence time may favour the rowth and blooming of cyanobacteria, especially the toxin-producing ones such as Microcystis spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the increase in concentrations an increase in BL and BW was observed. These results suggest that changes in the body structure of zooplankton are caused by increases in salinity (Brucet et al, 2010).…”
Section: Allometric Changes In S Mucronatamentioning
confidence: 71%